Implementasi Digital Public Relations Senyum World Hotel Kota Wisata Batu dalam Membangun Citra di Media Sosial Instagram - Rinata, Asfira Rachmad; Romadhan, Mohammad Insan; Christie, Cindy Intha (Universitas 17 Agustus 1945 Surabaya, 2026)
The development of digital technology has significantly transformed public relations practices, particularly within the hospitality industry. Social media has become a primary medium for building relationships, organizational image, and reputation through a Digital Public Relations approach. Instagram is one of the most widely used social media platforms due to its visual and interactive characteristics. This study aims to analyze the implementation of Digital Public Relations through Instagram at Senyum World Hotel Batu and to identify the challenges encountered in its execution. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that Senyum World Hotel Batu has implemented Digital Public Relations via Instagram by utilizing visual content, engaging with audiences, and leveraging Instagram features such as feeds, stories, reels, and hashtags. Digital PR activities are primarily focused on information dissemination, hotel image formation, and relationship building with the public. However, challenges in implementing digital public relations include limitations in human resources, the need for more comprehensive content planning, and maintaining content consistency. This study concludes that Instagram plays a crucial role as a Digital Public Relations medium in building a positive image and maintaining relationships with the public; nevertheless, more structured and sustainable management strategies are required. Keywords: Digital Public Relations, Social Media, Hospitality Industry, Brand Image